"Muy bien" as a transition token in teacher-student interactions in the Spanish as a foreign language classroom. (April 2021) - Batlle, Jaume
Abstract: In foreign language teaching, teacher discourse plays a fundamental role in managing the actions carried out in class. The teacher generally manages student participation in interactional activities by formulating questions, proposing topics of conversation or directly identifying the next speaker, using a series of verbal and nonverbal actions to direct turn-taking. The study presented here analyses the use by the teacher of the expression "muy bien" – equivalent to the English "very good" or "ok", among other translations – in a series of interactions with students in a meaning-and-fluency context in the Spanish as a foreign language classroom. The results show that "muy bien" is used as a transition token between speakers, as a means of focusing the attention of the interaction or IRF sequence, or as a transition token between activities. Detailed analysis demonstrates the interactional complexity of the use of "muy bien", an expression that should be considered a key element in didactic discourse and teacher training.